EARLY WARNING OF WEATHER SERVICES OF AIRPORTS ABOUT STORMS WITH USE PARAMETRIC ARRANGEMENT OF RECEPTION OF INFRA-AUDIBLE ON ULTRASONIC AND MICROWAVE BORING BEAMS - S. A. Dubyanskiy (Научный вестник МГТУ ГА, 2016)
The method of early warning of weather services of airports about storms with use parametric arrangement of reception of infra- audible on ultrasonic and microwave boring beams are considered.